2020
DOI: 10.1007/s00709-020-01548-3
|View full text |Cite
|
Sign up to set email alerts
|

The expression of miRNA encoded by C19MC and miR-371-3 strongly varies among individual placentas but does not differ between spontaneous and induced abortions

Abstract: miRNAs of the largest human miRNA gene cluster at all, i.e., C19MC, are almost exclusively expressed in the placenta. Nevertheless, only little is known about the interindividual variation of their expression and even about possible influence of gestational age, conflicting data is reported as well as for miRNAs of the much smaller miR-371-3 cluster. Our present study aims at the analyses of the expression of miRNAs from both clusters at different times of pregnancy, possible differences between placenta sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…There was a 20-fold increase in miR-517a , which partly coincided with the study by Gottlieb et al [55, 121]. Furthermore, Wang et al showed elevated expression of miR-517a-3p in the decidual tissue and chorion of the trophoblast in women with multiple miscarriages, which was similar to the results by Gottlieb et al [55, 122].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…There was a 20-fold increase in miR-517a , which partly coincided with the study by Gottlieb et al [55, 121]. Furthermore, Wang et al showed elevated expression of miR-517a-3p in the decidual tissue and chorion of the trophoblast in women with multiple miscarriages, which was similar to the results by Gottlieb et al [55, 122].…”
Section: Resultssupporting
confidence: 85%
“…C19MC miRNAs are among the most highly expressed miRNAs in the human placenta and the serum of pregnant women [114, 115]. The study by Gottlieb et al investigated if the occurrence of miscarriage is affected by miR-371-3 cluster, which crosses the maternal–fetal barrier [55]. Unfortunately, there was no confirmation of this hypothesis, and significant differences in the expression of any of the miRNA molecules tested, including miR-371-3 cluster, could not be obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In primary trophoblasts isolated from normal term placentas, 41 out of the 46 C19MC miRNA genes were expressed and they represented the majority of miRNAs expressed in these cells as well as in the exosomes secreted by them ( Luo et al, 2009 ; Donker et al, 2012 ; Lee et al, 2016 ). Temporally, studies have shown that C19MC miRNAs exhibit a dynamic gestational expression profile ( Gottlieb et al, 2021 ); however, there are inconsistencies among different reports. One study showed that 46 mature C19MC miRNAs were higher in third trimester villous trophoblasts compared to first trimester cells ( Donker et al, 2012 ; Morales-Prieto et al, 2012 ), while another study showed that the expression of some C19MC members were higher in first trimester samples (ranged 6–10 weeks) than in second trimester ones (ranged 11–23 weeks) ( Smith et al, 2021 ).…”
Section: Microrna Regulation Of Trophoblast Invasion Spiral Artery Re...mentioning
confidence: 99%